In search of self in India and Japan : toward a cross-cultural psychology - Roland, Alan, 1930-2023 (Princeton University Press, 1988)
"This book addresses a fundamental question - the universality of human nature ... Drawing upon work with patients and therapists in both India and Japan, he describes the profound difference between the Western individualized self and the familial self so central to Asian culture ... Of particular value is Roland's sensitive treatment of the evolving identity of women in the two cultures, as well as his exploration of the deeply significant spiritual self, a topic that is largely neglected in Western theory and practice."--Choice.